Luisterrijk der letteren - Bernaerts, Lars (Academia Press, 2019)
Luisterrijk der letteren offers an overview of the intensive interfaces between the literary field and radio in the Low Countries. The subsequent chapters treat original radio plays of Walter van den Broeck and Ivo Michiels, among others, as well as translations of German and English radio plays, and adaptations like that of Herman Teirlinck's play De vertraagde film. Contributions about Dutch radio plays from the interbellum and experimental verbosonies of Ab van Eyk enforce the image of a genre that continuously renews itself in interaction with literature. Finally, the reader is offered an overview of post-war literary radio plays. Thus, this book shows and investigates for the first time the profusion of literary radio plays in Flanders and the Netherlands.
Keywords: Dutch literature; Children's writings, Dutch